Pengaruh Implementasi Kurikulum Merdeka Dan Kesiapan Siswa Terhadap Efektivitas Pelaksanaan Pembelajaran Ekonomi Di SMAN 1 Pakel Tulungagung - Umami, Nailariza; Hartanti, Sabrina Putri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The research aims to assess the impact of the Implementation of the Merdeka Curriculum and students' readiness on the effectiveness of economic learning in SMAN 1 Pakel Tulungagung. The method use was a quantitative descriptive with population of 322 X class students at SMAN 1 Pakel Tulungagung, and used a sample of 90 students. In data collection we use the questionnaire/query, while to analyze the data we use multiple linear regression techniques. Data analysis shows that the implementation of the Merdeka curriculum has a significant impact on the effectiveness of economic learning in SMAN 1 Pakel Tulungagung. A thitung value of (15.414) is greater than a table (1.987) with a significance level of 0.000 ± 0.05. Thus, the implementation of the Merdeka curriculum has a positive impact on improving the effectiveness of economic learning in that school. However, research results also show that there is no significant influence between student readiness and the effectiveness of economic learning implementation. The thitung value (0.94) is smaller than the tttable (1.987), with a significance value of 0.925 ± 0.05. This indicates that students' readiness does not have a significant effect on the effectiveness of economic learning at SMAN 1 Pakel Tulungagung. The F-test showed that F-count (222.606) was larger than F-table (3.10) with a significance level of 0.000 ± 0.05. This result confirms that overall, the implementation of the Merdeka curriculum and students' readiness together have a significant effect on the effectiveness of economic learning implementation in SMAN 1 Pakel Tulungagung